Drone detection by neural network using SURF feature and GLCM method - Ahmed, Tanzia; Roy, Bir Ballav; Rahman, Tanvir (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.